The Effect of Field Study Implementation on the Critical and Creative Thinking Skills of Pre-Service Science Teachers - Geterudis Kerans; Yulita Adelfin Lede; Khristoforus Palli Ngongo; Angela Ghunu; Falentina Tamo Ina (Universitas Lambung Mangkurat, 2026)
Learning processes implemented in higher education institutions must be student-centered. Such processes provide opportunities for students to actively engage in learning activities, enabling them to acquire understanding and skills aligned with the intended learning objectives. To achieve this condition, active learning methods are required, one of which is the Field Study method. The purpose of this study is to analyze the effect of the Field Study method on the critical and creative thinking skills of pre-service science teachers. This study employed a quasi-experimental design using a one-group pre-test–post-test approach. The effect of the method on students’ critical and creative thinking skills was examined through pre-test and post-test scores. The results indicate that the Field Study method has a positive effect on improving students’ critical and creative thinking skills, as evidenced by the pre-test and post-test scores. The Wilcoxon test results for pre-test and post-test scores on students’ critical and creative thinking skills show a Sig. (2-tailed) value of 0.000, indicating a significant difference between pre-test and post-test scores. In conclusion, the Field Study method significantly enhances students’ critical and creative thinking skills and is appropriate for use in exploring subject matter related to real-world problems encountered by students. The implication for future science education is that the Field Study method can be effectively applied to learning activities involving real-life issues surrounding students. Science education is not solely concerned with theoretical knowledge but also with developing the ability to critically analyze problems and generate creative solutions.